The Substitution Effects of Tapioca Starch and Beetroot Powder as Filler On The Physical and Sensory Characteristics Of Chicken Sausage - Winny Swastike; Edi Suryanto; Rusman Rusman; Chusnul Hanim; Jamhari Jamhari; Yuny Erwanto; Jumari Jumari (Faculty of Animal Science Universitas Brawijaya, 2020)
Red beetroot is rich in phenolic acids and betalain as natural food-coloring agents. Freeze-dried red beetroot that ground into powder can be used as a source of natural coloring to substitute the use of synthetic food color additives as well as filler to substitute tapioca. This study evaluates the function of red beetroot powder not only as filler but also as coloring agent on chicken sausage. Furthermore, its effects as filler (tapioca and beetroot) were also observed on the physical and sensory characteristics of the produced chicken sausage. The substitution of tapioca flour and beetroot powder in this study were 18:0, 17:1, 16:2, and 15:3 (%:%). Each treatment was consisted of three replications. The examined physical properties include pH, water-holding capacity (WHC) and sensory properties. The study found that WHC, color, texture profile and sensory properties were influenced by the increasing level of beetroot flour ratio, while different ratios had no effect on the pH. Chicken sausages made with higher ratio of beetroot flour had good acceptability on flavor and color. The conclusions of this study were substitution tapioca with 2% beetroot powder influenced physical quality (water holding capacity and tenderness) and sensory (color and flavor) of chicken sausage.